Female sexuality : new psychoanalytic views - Chasseguet-Smirgel, Janine, 1928-2006.; Luquet-Parat, C. J. (Catherine J.); Wyatt, Frederick, 1911-1993. (London : Karnac, 1992)
Contains six essays and an introduction on Freudian and non-Freudian views of female sexuality. Contributors include Joyce McDougall, Maria Torok and Bela Grunberger.
COVER; Contents; Introduction; A Masculine Mythology of Femininity; Outline for a Study of Narcissism in Female Sexuality; The Change of Object; Feminine Guilt and the Oedipus Complex; The Significance of Penis Envy in Women; Homosexuality in Women; Notes
Print version record.
Includes bibliographical references.
English.
eBooks on EBSCOhost
Keywords: Women -- Psychology; Psychoanalysis; Women -- Sexual behavior; Femmes -- Psychologie; Psychanalyse; Femmes -- Sexualité.; psychoanalysis; PSYCHOLOGY -- Human Sexuality; Psychoanalysis; Women -- Psychology; Women -- Sexual behavior